PELATIHAN PEMASARAN MENGUNAKAN PLATFORM E-COMMERCE : MARKETING TRAINING USING E-COMMERCE PLATFORM - syafril; Hidayat, Taufik; Syaffitri, Nabila Ahya; Sahal, Luthfi; Asyahri, Yusuf; Syaffutra, Ryanizard Arya; As-Syahri, Hidayatullah (IHSA Institute, 2024)
This community service activity was held in collaboration between the Entrepreneurship and Career Services Unit (UPKK) of UIN Antasari and professional Micro, Small and Medium Enterprises (MSMEs) who are members of various organizations. This service activity was carried out in the form of a workshop for participants about entrepreneurship using an e-commerce platform. The method used in this service activity is a presentation of the material presented, followed by a discussion and question and answer session. As a result of this community service, it is hoped that participants will be able to understand business through e-commerce platform media. Furthermore, it is hoped that the participants will be able to start their business using the e-commerce platform that has been learned during this workshop.